2016
DOI: 10.1016/j.vaccine.2016.04.081
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding the mechanism underlying the strong adjuvant activity of aluminum salt nanoparticles

Abstract: Aluminum salts such as aluminum oxyhydroxide and aluminum hydroxyphosphate are commonly used human vaccine adjuvants. In an effort to improve the adjuvant activity of aluminum salts, we previously showed that the adjuvant activity of aluminum oxyhydroxide nanoparticles is significantly more potent than that of aluminum oxyhydroxide microparticles. The present study was designed to i) understand the mechanism underlying the potent adjuvant activity of aluminum oxyhydroxide nanoparticles, relative to micropartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 36 publications
1
60
0
Order By: Relevance
“…Similarly, we also showed that the AH-NPs (majority below 100 nm) are more potent than the AH-MPs (X 50 , 5.36 μm) in activating NLRP3 inflammasome [3]. Based on the findings, we concluded that the mechanism underlying the stronger adjuvant activity of aluminum salt nanoparticles is likely related to their stronger ability to activate the NLRP3 inflammasome than aluminum salt microparticles [3]. …”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Similarly, we also showed that the AH-NPs (majority below 100 nm) are more potent than the AH-MPs (X 50 , 5.36 μm) in activating NLRP3 inflammasome [3]. Based on the findings, we concluded that the mechanism underlying the stronger adjuvant activity of aluminum salt nanoparticles is likely related to their stronger ability to activate the NLRP3 inflammasome than aluminum salt microparticles [3]. …”
mentioning
confidence: 84%
“…The paper commented by Mold et al was designed to understand the potential mechanism underlying the stronger vaccine adjuvant activity of AH-NPs, relative to AH-MPs, and to test whether aluminum phosphate nanoparticles also have a stronger adjuvant activity than aluminum phosphate microparticles [3]. We prepared aluminum phosphate nanoparticles (AP-NPs, 122–255 nm) and aluminum phosphate microparticles (AP-MPs, X 50 , 4.87 μm), and showed that the AP-NPs are more potent than the AP-MPs in activating NLRP3 inflammasome [3]. Similarly, we also showed that the AH-NPs (majority below 100 nm) are more potent than the AH-MPs (X 50 , 5.36 μm) in activating NLRP3 inflammasome [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum is a constituent of antacids, deodorants and food additives, thus allowed its easy access into the body. Excessive Al intake leads to accumulation of Aβ in the brain and over expression of β-amyloid precursor protein [11]. The neurotoxicity of Aβ is strongly related to oxidative stress which plays an effective role in the pathogenesis of AD [12].…”
Section: Modeling Stages Of Alzheimer's Disease In Ratsmentioning
confidence: 99%
“…20 It has been shown that the NLRP3 inflammasome is activated by classical adjuvants, including aluminum hydroxide and saponin, which requires both Toll-like receptor (TLR) and NLRP3 signaling in APCs. [21][22][23][24] Following the recruitment and activation of caspase-1 in the NLRP3 inflammasome pathway, the biologically inactive precursor pro-IL-1β is processed into IL-1β. In fact, chitosan or SiO 2 nanoparticles are known to trigger caspase-1 cleavage and IL-1β secretion in macrophages and keratinocytes, which are mediated by the NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 99%